Efficient in vitro Regeneration of Brassica napus L. Var. BARI Sorisha-18 (Plant Tissue Culture and Biotechnology, 2023)
Brassica is one of the most nutritious and significant oil yielding crop plants around the world, including in Bangladesh. However, the development of a smart variety with a short maturity duration and high yield is a need of the present day. To achieve that, both genetic transformation and genome editing can be promising technologies for improvement, and establishment of suitable regeneration systems is a pre-requisite to deploy such technique. For this reason, an efficient and reproducible in vitro regeneration protocol for Brassica napus L. var. BARI Sorisha-18 was developed using MS medium supplemented with various concentrations and combinations of 2, 4-D, BAP and NAA. The highest frequency of in vitro regeneration of multiple shoots was obtained on MS medium supplemented with 1.0 mg/l BAP and 0.1 mg/l NAA from both cotyledonary leaf attached with petiole and hypocotyl explants. The elongation of shoots was also achieved with the same media composition. Half strength of MS medium supplemented with 0.2 mg/l IBA was found to be more effective in producing effective roots than other hormonal supplements applied. Following the development of effective roots, in vitro raised plantlets were successfully transplanted into the soil.Plant Tissue Cult. & Biotech. 33(2): 107-114, 2023 (December)